Imagens em Estilhaços : Toada do Esquecido de Ricardo Guilherme Dicke - Souza, Ederson Fernandes de (2012)
The narratives of Ricardo Guilherme Dicke exceeded the limits of the borders of the state of Mato Grosso, being appreciated by scholars and researchers from different parts of Brazil. Here we highlight the Forgotten Melody (2006) novel consists of 133 pages with breakneck plot. In our work we address the significance of symbolic images in the narrative, analysis grounded in Imaginary Studies Gilbert Durand.Estas symbolic representations are provided for the creation of imagery novelist, engendered in a desert setting, with no one and esturricados fields, thus building , the interior of Mato Grosso. The characters are crazed, others are thieves fortune, transformed into fugitives, traveling by land deserted, submitted by a covenant of life and death, the mandatory use of masks, this prohibition regimented in the preservation of life itself. We proved that this masking has the function of oblivion, meeting the central image of the narrative, the backcountry-Mato Grosso, we also observed that it emerges from the other images: death, oblivion, crossing, greed, fear among others.